CYLINDRICAL SHELL ANALYSIS OF REACTOR PRESSURE VESSEL FOR RDE - Sri Sudadiyo (Website, 2021)
CYLINDRICAL SHELL ANALYSIS OF REACTOR PRESSURE VESSEL FOR RDE. The present study deals with the design process analysis of cylindrical shell for Reactor Pressure Vessel (RPV) of Reaktor Daya Eksperimental (RDE). The RDE is prepared by BATAN for nuclear technology provider in Indonesia. RPV is a container for confining helium gas at elevated pressure and temperature (circa 700 °C). In RPV operation, mechanical stresses act as in consequence of internal pressure (3 MPa), external pressure, and different loads due to dead weight and helium content load. Therefore, if the RPV could not retain its material strength or exceed the maximum allowable shear stress it will cause failure. The applications and validity of Fortran code (RPV_RDE.exe) for the design analysis are represented by two simulation cases, which indicate good calculation results of design outputs compared to analytic solutions. Design outputs have met the safe requirements for the minimum wall thickness of cylindrical shell in upper portion of 60 mm and in lower portion of 100 mm, respectively.